1989
DOI: 10.1103/physreva.39.4274
|View full text |Cite
|
Sign up to set email alerts
|

Alternative interpretation of the double atomic-field bremsstrahlung experiment

Abstract: A recent experiment reported a two-order-of-magnitude enhancement of the cross section for double atomic-field bremsstrahlung when compared to various theoretical formulations. In this paper we propose to explain the observed coincidence rate in terms of the coherent emission of two thick-target bremsstrahlung photons from the Mylar vacuum window by electrons elastically scattered in the target. The photon energy dependence of the coincidence rate predicted by this thicktarget double bremsstrahlung (TTDB) mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…10. Second, following the reasoning put forward by Lehtihet and Quarles, 14 we have calculated the (effective) cross section of the predicted alternative process as shown by the dashed lines in Figs. 1 and 2.…”
Section: Nyi Dkidilimentioning
confidence: 99%
“…10. Second, following the reasoning put forward by Lehtihet and Quarles, 14 we have calculated the (effective) cross section of the predicted alternative process as shown by the dashed lines in Figs. 1 and 2.…”
Section: Nyi Dkidilimentioning
confidence: 99%
“…This was undertaken by Lehtihet and Quarles [7][8][9]. A wide variety of background processes were identified and considered; finally, it was suggested that the large experimental cross section could have arisen from a rather complicated process.…”
mentioning
confidence: 99%
“…Theoretical activity was stimulated by a series of experiments [26][27][28][29][30][31][32][33] in which the data on the 2BrS cross section and angular distribution were obtained for relatively high energies of the incident electron and emitted photon (up to 70 keV). Apart from the early work of Smirnov [34], where the 2BrS process was treated in terms of the relativistic first Born approximation (see also [35]), theoretical investigations were based on second order non-relativistic perturbation theory.…”
Section: Introductionmentioning
confidence: 99%